KEKUATAN BAMBU BETUNG (Dendrocalamus asper Backer ex K.Heyne) MENAHAN GAYA NORMAL TEKANAN DAN TARIKAN - Naresworo Nugroho; Effendi Tri Bahtiar; Arya Budhijatmiko Lelono (Jurnal Penelitian Hasil Hutan, 2022)
Bamboo is multifunctional forest product that can be used as furnitures, crafts, music instruments, and construction materials.The value of the compressive and tensile strength of bamboo has been used in construction design, but it is still limited, for exampleas a column or concrete reinforcement. This research aimed to determine the mechanical properties of a four years old betung bamboo(Dendrocalamus asper Backer ex K.Heyne,) specifically, compression strength parallel to grain, tension strength parallel andperpendicular to grain, and its 5% lower limit value. The sample size and mechanical properties testing refers to ISO 22157-2019. Compression and tension strength parallel to the grain were tested using UTM SATEC/Baldwin, while tension strengthperpendicular to the grain was tested using UTM Chun Yen. The data were analyzed using Easyfit 5.5 to obtain 5% lower limitvalue of each test. The average value of compression strength and tension strength parallel to grain were 53 N/mm² and 109N/mm², respectively. The average value of tension strength perpendicular to grain for 25 and 40 mm testing hole were 2.53 and1.19 N/mm², while average MOE value of compression and tension strength parallel to grain were 2,674 and 9,542 N/mm²,respectively. The 5% lower limit value of compression strength parallel to grain was 38.1 N/mm², tension strength parallel to grain61.8 N/mm², and 0.60 N/mm² for tension strength in perpendicular to grain. The 5% lower limit MOE value of compressionand tension strength parallel to grain were 1,105 and 6,076 N/mm², respectively.